Abductive Reasoning Logical Investigations into Discovery and Explanation - Aliseda, Atocha (Synthese Library, Studies in Epistemology, Logic, Methodology, and Philosophy of Science, 2006)
Abductive Reasoning: Logical Investigations into Discovery and Explanation is a much awaited original contribution to the study of abductive reasoning, providing logical foundations and a rich sample of pertinent applications. Divided into three parts on the conceptual framework, the logical foundations, and the applications, this monograph takes the reader for a comprehensive and erudite tour through the taxonomy of abductive reasoning, via the logical workings of abductive inference ending with applications pertinent to scientific explanation, empirical progress, pragmatism and belief revision. "The book is an excellent contribution to the study of abductive reasoning. It applies logical techniques to important problems in the philosophy of science. The new results are also interesting for artificial intelligence." Prof. Ilkka Niiniluoto, University of Helsinki, Finland.